2019
DOI: 10.1186/s13568-019-0846-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Piromyces sp. CN6 CGMCC 14449 on fermentation quality, nutrient composition and the in vitro degradation rate of whole crop maize silage

Abstract: This study investigated the effects of the rumen fungus Piromyces sp. CN6 CGMCC 14449 as a silage additive on the fermentation quality, nutrient composition and in vitro digestibility of whole crop maize silage. Whole crop maize served as the silage material and was vacuum packed in polyethylene bags. Three ensiling treatments were applied: a control (CK), addition of a fungus (FU) at 10 5 thallus-forming units per gram, and addition of compound enzyme (EN) at 0.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 46 publications
0
22
1
3
Order By: Relevance
“…Consequently, plant biomass like straw that is yet widely unexploited in ruminant nutrition could get upvalued and therefore become a more extensively used diet component in ruminant livestock production systems. Such a mode of action was already indicated by two pilot studies investigating the impact of AF inoculation on quality and ruminal degradation of rice straw or whole crop maize silage [ 81 , 82 ]. The plant materials were ensiled with AF strains isolated from herbivore guts, which in both approaches led to an increased ruminal dry matter and fiber degradability during subsequent incubations either in vitro [ 82 ] or in situ [ 81 ].…”
Section: Anaerobic Fungi As Silage Additivesmentioning
confidence: 88%
See 3 more Smart Citations
“…Consequently, plant biomass like straw that is yet widely unexploited in ruminant nutrition could get upvalued and therefore become a more extensively used diet component in ruminant livestock production systems. Such a mode of action was already indicated by two pilot studies investigating the impact of AF inoculation on quality and ruminal degradation of rice straw or whole crop maize silage [ 81 , 82 ]. The plant materials were ensiled with AF strains isolated from herbivore guts, which in both approaches led to an increased ruminal dry matter and fiber degradability during subsequent incubations either in vitro [ 82 ] or in situ [ 81 ].…”
Section: Anaerobic Fungi As Silage Additivesmentioning
confidence: 88%
“…Although these data provide first evidence of the AF potential as silage additives, it has to be noted that the two studies [ 81 , 82 ] on AF-treated silages were conducted at minor lab-scale. Immense quantities of AF cultures would be necessary to inoculate the large volumes of forage material sufficiently, which are moreover ensiled in very few days on cattle farms.…”
Section: Anaerobic Fungi As Silage Additivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of nutrient metabolism in the substrate can reflect the rumen microbial activity, as well as the fermentation degree of the substrate [26]. Jin et al [13] demonstrated that U. cannabina can be used as the replacement for the traditional feed mixture of forage in the feeding experiments.…”
Section: U Cannabina To L Chinensis Ratios On Substrate Degradationmentioning
confidence: 99%